Tinjauan Terhadap Konsep Keadilan Spasial Dan Partisipasi Masyarakat Dalam Perencanaan Dan Pengendalian Pemanfaatan Ruang Pada Program Normalisasi Ciliwung Di Provinsi DKI Jakarta - Hexagraha, Shafira Anindia Alif; Setyorini, Savitri Nur (UI Scholars Hub, 2019)
The idea of public interest in spatial planning is a two-sided claim. The government often uses it to enforce spatial plan program without the consent of the affected groups. On the other hand, the affected groups also use it as their defense to protect their damaged rights. The idea of spatial justice is derived from progressive intellectual tradition that is highly aware of the severeness of injustice in urban spaces and hence demands radical reconception of spaces, governance, and spatial planning. Most influential intellectual tradition in spatial justice are Habermas’ Public Sphere, Harvey’s Right to The City, and Lefebvre’s Production of Space which emphasize on active public participation in urban policy making especially for the marginalized groups who experience exacerbated inequality the long standing urban policies have produced.